1998
DOI: 10.1104/pp.117.2.619
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Quantum Yield of Photoinhibition Contributes to Copper Toxicity in Vivo1

Abstract: The effect of copper on photoinhibition of photosystem II in vivo was studied in bean (Phaseolus vulgaris L. cv Dufrix). The plants were grown hydroponically in the presence of various concentrations of Cu 2؉ ranging from the optimum 0.3 M (control) to 15 M. The copper concentration of leaves varied according to the nutrient medium from a control value of 13 mg kg ؊1 dry weight to 76 mg kg ؊1 dry weight. Leaf samples were illuminated in the presence and absence of lincomycin at different light intensities (500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 38 publications
0
66
1
2
Order By: Relevance
“…it is severely toxic to cells (Marschner 1995). Reduction in biomass, symptoms of chlorosis, decline in pigment content and alterations in the chloroplast and thylakoid ultrastructure have been reported (Baszynski et al 1988, Patsikka et al 1998 in plants under Cu stress. Toxic concentration of Cu results in generation of reactive oxygen species (ROS) like hydrogen peroxide, superoxide radical, and hydroxyl radical that exerts oxidative stress in cells (Panda et al 2003).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…it is severely toxic to cells (Marschner 1995). Reduction in biomass, symptoms of chlorosis, decline in pigment content and alterations in the chloroplast and thylakoid ultrastructure have been reported (Baszynski et al 1988, Patsikka et al 1998 in plants under Cu stress. Toxic concentration of Cu results in generation of reactive oxygen species (ROS) like hydrogen peroxide, superoxide radical, and hydroxyl radical that exerts oxidative stress in cells (Panda et al 2003).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…The extent of photo-inhibition (Y, %) was calculated according to Pätsikkä, Aro & Tyystjärvi (1998).…”
Section: Photo-inhibitory Treatment and Dark Recoverymentioning
confidence: 99%
“…Previous studies showed that nano copper depleted PSII action centers, leading to photoinhibition 25 and disruption of the repair cycle. 33,34 In addition, stomatal conductance and transpiration rates tended to increase in nCu treatments compared to the control. The actual mechanism for Cu to increase stomatal conductance and transpiration rate is still unknown.…”
Section: Photosynthesis and Biomass Accumulationmentioning
confidence: 99%